Efficacy of mifepristone in the management of fibroid - R., Priyanka; P. B., Hiremath; Sekar, G. Sindhujha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Uterine fibroids are the most common benign tumors of the uterus. The incidence has been shown to be as high as 70–80 percent in studies using histologic and sonographic examinations. Majority of fibroids are asymptomatic and when symptomatic, patients present with menstrual disturbances, infertility, lump abdomen or pressure effects. The complications associated are severe anemia, hyaline or red degeneration, urinary retention, hydronephrosis secondary to obstructive uropathy and rarely sarcomatous changes. The treatment depends upon the size, symptoms, location and age of the patient. The aim and objective of this study is to evaluate the effectiveness of Mifepristone in symptomatic improvement and reduction of the size of fibroid. Methods: The study was conducted in Sri Venkateswaraa Medical College Hospital and Research Centre (SVMCH and RC), Puducherry. This is a hospital based longitudinal study conducted in between December 2019 to June 2021 for a period of 18 months. 30 consecutive cases were studied based on inclusion criteria. All patients were treated with mifepristone 50 mg once weekly for 6 months. Analysis was performed by using statistical package for the social sciences (SPSS) version 23 software. Results: In this study we observed there was a significant improvement in the hemoglobin (Hb) level, significant reduction in uterine volume, fibroid size and endometrial thickness after 6th month follow-up. Conclusions: Mifepristone was able to significantly improve the patient outcome by reducing the amount of blood flow during menstruation and increasing the Hb levels and significantly reduce the size of myoma.